Establishing indicators of biological integrity in western Namibia rangelands. - Zeidler, Juliane (My University, 1999)
An Index of Biological Integrity (IBI) has been developed for rangeland condition assessment in arid northwestern Namibia. The usefulness of termites as bio-indlcators has been tested and reliable sampling protocol for termite diversity in an arid ervlronrnent has been developed. The study was conducted mainly at a high- and low-intensity site on each of three farms. Two of the farms were communally owned; the other was commercially owned. (Abbreviation abstract)
A thesis submitted to the Faculty of Science, University of the Witwatersrand, .Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy.
Keywords: Rangelands -- Namibia.; Land capability for agriculture -- Namibia.; Soil microbiology -- Namibia.; Soil profiles -- Namibia.; Soils.